2013
DOI: 10.1155/2013/515636
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Hepatitis C Infection among Current And Former Injection Drug Users within a Multidisciplinary Treatment Model at a Community Health Centre

Abstract: The aim of the present prospective observational study was to assess uptake and success of hepatitis C virus (HCV) treatment among a group of former and current injection drug users with chronic HCV infection at the Street Health Centre in Kingston, Ontario. The Street Health Centre offers hepatitis C education, assessment and treatment within a multidisciplinary, integrated and collaborative treatment model of care delivered by primary care professionals. The study enrolled a convenience sample of 34 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…These studies demonstrated that patients with ongoing drug use and psychiatric comorbidity-- those traditionally excluded from systems of care-- can be effectively linked to care from and sometimes treated within these settings (Bruce et al, 2012; Jack, Willott, Manners, Varnam, & Thomson, 2009; McAllister et al, 2014; Morano et al, 2014; Newman et al, 2013; Seidenberg et al, 2013). One study implemented an integrated, multidisciplinary medical group visit to integrate care (Ho et al, 2013).…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
“…These studies demonstrated that patients with ongoing drug use and psychiatric comorbidity-- those traditionally excluded from systems of care-- can be effectively linked to care from and sometimes treated within these settings (Bruce et al, 2012; Jack, Willott, Manners, Varnam, & Thomson, 2009; McAllister et al, 2014; Morano et al, 2014; Newman et al, 2013; Seidenberg et al, 2013). One study implemented an integrated, multidisciplinary medical group visit to integrate care (Ho et al, 2013).…”
Section: Results: Intervention Strategiesmentioning
confidence: 99%
“…This is also particularly important given the potential risk for HCV reinfection following HCV treatment. Although the reported rates of HCV reinfection to date have been low (7, 40), continued risk reduction education will be important as interferon-free regimens are expanded to populations of PWID who might be at greater risk for re-exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Again, British Journal of General Practice, December 2013 e847 Table 1 small numbers was a feature of the study, but further evidence of the potential for success was demonstrated. 18 The evidence would suggest that support needs to be offered to those who use drugs to engage with, and remain in, primary care-based treatment. Charlebois et al reported the effects of peer support in a multidisciplinary team in Toronto.…”
Section: Qualitative Studiesmentioning
confidence: 99%